The Authority of Endorsements of Legislations for Iraqi Constitution in 2005 - Zaid, Hind Kamil Abd (International Journal of Psychosocial Rehabilitation, 2020)
The research seeks to identify the competence of the ratification of legislation under the 2005 Constitution in the Iraqi political system under the parliamentary system applied in Iraq after 2003, and the work by which the head of state gives the necessary declaration without which the law cannot become enforceable, and thus ratification is a key element In the legislative process, it is a birth certificate of the legislation to be supported by its implementation, issued by the President of the Republic and includes an order for all members of the executive branch and its workers to implement the new law after the approval of the draft law Parliament does not become effective legislation only after ratified by the Head of State And it`s. Following the issuance process, the publication of the law on the order of the President of the State in the Official Gazette, but the issuance and publication are two separate processes are integrated into the publishing process so that some people confuse them and calculate that the publication is the issuance, while the issuance of the pre-publication, and publication follows the issuance. Publication is a material process subsequent to the issuance intended to notify the public of the enforcement of the law on a certain date, i.e. to inform the law to the people and inform them. The 2005 constitution gave the president the power to ratify and promulgate laws, and it seems to us that the president's power to ratify laws is more formal than actual. Legislation is ratified by a 15-day period from the date of referral to the president if he does not actually ratify it. It is noticeable that there is a constitutional breach that has arisen under the State Administration Law for the Transitional Period, where the Vice-President exercised the power to ratify the laws referred to the Head of State in case the President is absent or refuses to ratify. More accurate by the vice president instead of the president's Central Criminal Court. It is forbidden to abstain from ratification, as indicated in the text of article (75 / second) of the Constitution by saying the Vice President replaces the President of the Republic in his absence.